THE ROLE OF LIBRARIES IN THE LEARNING PROCESS OF ELEMENTARY SCHOOL STUDENTS - Prasetia, Anggi; Syahrilfuddin, Syahrilfuddin; Mulyani, Eva Astuti Mulyani (IKIP Siliwangi Bandung, 2023)
The library is an integral part of a school, as well as a source of learning and a medium of self-development for students in literacy activities. But in practice, it still has problems, such as a lack of a sincere understanding of the role and function of school libraries in the quality learning process. This study aims to describe the role of libraries as learning resources for elementary school students. In addition to the quality of student literacy at SDN 011 Bangko Bakti, Rokan Hilir Regency. This research uses a descriptive quality approach, with interview techniques to students, library managers, principals, and class teachers. Data analysis techniques used with data collection, data reduction, displaying data and drawing conclusions. Test the validity of the data, namely by triangulation technique. The results of the study revealed that the role of school libraries as a source of learning for elementary school students has a close relationship between the two, libraries with a good management system tend to influence students' interest in visiting and using the library as a means of learning and also refer to the quality of the impact of literacy. This is studied through the results of interview analysis data and observations.